Kontribusi Dan Peran Polisi Militer Dalam Menegakkan Hukum Dan Keadilan Dalam Lingkungan Tentara Nasional Indonesia - Debby Nauli Rafeyfa Simanjuntak; Alifio Kadafi; Bagas Jeremia Siahaan; Divany Harbina Emzilena Kaban; Faiz Aryaputra; Nadira Fariza Sukma; Putri Galuh Pitaloka; Sinta Ramadhani; Thalia Salma Putri Kamilah (Jurnal Relasi Publik, 2024)
As a sovereign and independent country, Indonesia has national goals it aspires to achieve, one of which is to maintain and promote world order. This can be implemented on a smaller scale, such as within the Indonesian National Armed Forces. This research is normative in nature, gathering data through literature studies. The results indicate that military police play a role within the Indonesian National Armed Forces. However, there are still many challenges faced by the military police in enforcing law and justice within the Indonesian National Armed Forces.